Combined Effects of Microplastics and Benzo[a]pyrene on the Marine Diatom Chaetoceros muelleri - Su, Yuanyuan; Qi, Huaiyuan; Hou, Yipeng; Gao, Mengyi; Li, Jie; Cai, Minggang; Zhu, Xiaoshan; Chen, Miao; Ge, Chengjun; Fu, Dongdong; Wang, Zezheng; Peng, Licheng (Frontiers in Marine Science, 2022)
Microplastics are regarded as ubiquitous pollutants in the ocean and have attracted worldwide concerns. Benzo[a]pyrene (B[a]P), one of typical polycyclic aromatic hydrocarbons (PAHs), is commonly detected in marine environment. Once coexisted, the microplastics and B[a]P may interact with each other and result in combined toxicity to organisms, and these remain to be systematically elucidated. Thus, this study aims to investigate i) the effects of single micro-sized polystyrene (mPS), polyethylene terephthalate (mPET), and B[a]P on cell growth of Chaetoceros muelleri; and ii) the interaction of microplastics and B[a]P, and their combined effects on C. muelleri. The results showed that both single microplastics and B[a]P at a high concentration of 150 μg/L inhibited the growth of C. muelleri. For single treatment of microplastics, stronger inhibition effects on microalgae was caused by mPET than that of mPS, with the highest IR of 25.23% and 11.17%, respectively. This may be attributed to the obvious surface roughness of mPET. By comparison, the combined effects of microplastics and B[a]P significantly inhibited the growth of C. muelleri as compared with the single treatment of B[a]P (P < 0.05). Synergistic effect was found in the combination of microplastics with B[a]P at high concentrations of 150 μg/L. Interestingly, the antagonistic effect on C. muelleri was observed the combined treatment of microplastics and B[a]P at low concentrations of 10 μg/L. In addition, the decreased superoxide dismutase (SOD) and catalase (CAT) activity in single and composite systems may indicate that the antioxidative enzymatic system of microalgae has been destroyed. This study will be helpful to further explore the ecological threats of microplastics and PAHs to the marine ecosystem.